PENGARUH ANTHESIS JANTAN DAN WAKTU POLINASI TERHADAP TINGKAT KEBERHASILAN PEMBENTUKAN BENIH SEMANGKA TANPA BIJI (Citrullus Lanatus Thunberg.) - Ahmad Ihwanudin; Sri Hartatik; Kacung Hariyono; Josi Ali Arifandi (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
Triploid watermelon seeds are produced from the crossing between watermelon diploid as males and tetraploid watermelons as females. The success of triploid seed formation is influenced by the success of pollination determined by pollen viability which is characterized by the period of anthesis and peptic receptivity by the time of pollination. This experiment was conducted in Jember  on 2018. The Factorial Randomized Block Design, 3x3  with three replications, was concucted to determine the effect of male anthesis period and pollination time on the success rate of seedless watermelon seed formation. The results showed that no significant interaction of the male anthesis period and the time of pollination effect. Pollens harvested during pre anthesis give the best pollination results. On the other hand, the best pollination can be done at 07.30 – 08.30 am  Keywords: anthesis, pollination, seeds, seedless watermelon.